Multifarious Effects of Arsenic on Plants and Strategies for Mitigation - Rahul Beniwal; Radheshyam Yadav; Wusirika Ramakrishna (Agriculture, 2023)
Arsenic contamination in soil and water is a major problem worldwide. Inorganic arsenic is widely present as arsenate and arsenite. Arsenic is transferred to crops through the soil and irrigation water. It is reported to reduce crop production in plants and can cause a wide array of diseases in humans, including different types of cancers, premature delivery, stillbirth, and spontaneous abortion. Arsenic methyltransferase (AS3MT) in the human body converts inorganic arsenic into monomethylarsonic acid and dimethylarsinic acid, which are later excreted from the body. Arsenic transfer from the soil to grains of rice involves different transporters such as Lsi1, Lsi2, and Lsi6. These transporters are also required for the transfer of silicate, which makes them important for the plant. Different mitigation strategies have been used to mitigate arsenic from crops, such as plant growth-promoting bacteria, fungi, and nanoparticles, as well as using different plant genotypes and plant extracts. Different factors such as nitric oxide, Fe, and jasmonate also affect the response of a plant to the oxidative stress caused by arsenic. This review highlights the various effects of arsenic on plants with respect to their biochemical, molecular, and physiological aspects and the employment of classical and innovative methods for their mitigation. The current review is expected to initiate further research to improve As remediation to mitigate the effect of heavy metal pollution on the environment.